Multitask sparse Learning based Facial Expression Classification - Nimbal, Pratik; Shyam, Gopal Krishna (International Journal of Computer Sciences and Engineering, 2019)
In today’s era, Facial Expression and recognition is a very challenging and fascinating subject with regards to field of AI and pattern recognition because of developmental psychology and human machine interface. For outward appearance designing classifiers with high reliability is a significant advance in this research. This paper represents a framework for person dependent expressions by combining all types of facial recognition types of facial by means of various multiple kernel learning in Support vector machines(SVM). We contemplated the impact of MKL for learning the piece loads and observationally assess the aftereffects of six fundamental expressions with impartial expression. included. In our investigations we have joined two mainstream facial element portrayals, dlib library and Multikernel SVM with polynomial kernel. Our experimental results on the cohn-Kanade face database as well as manually included database demonstrate that this framework out performs the state-of-arts, conventional techniques and straightforward MKL based multiclass SVM for facial expression recognition.